2004
DOI: 10.1210/jc.2003-031403
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Induces Natriuresis in Healthy Subjects and in Insulin-Resistant Obese Men

Abstract: Glucagon-like peptide-1-(7-36)-amide (GLP-1) is involved in satiety control and glucose homeostasis. Animal studies suggest a physiological role for GLP-1 in water and salt homeostasis. This study's aim was to define the effects of GLP-1 on water and sodium excretion in both healthy and obese men. Fifteen healthy subjects and 16 obese men (mean body mass index, 36 kg/m2) were examined in a double-blind, placebo-controlled, crossover study to demonstrate the effects of a 3-h infusion of GLP-1 on urinary sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
267
5
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(306 citation statements)
references
References 23 publications
14
267
5
11
Order By: Relevance
“…It was suggested that the increase in cardiac output may be a compensatory response to vasodilatation elsewhere. The effectiveness of GLP-1R agonists in reducing BP in clinical trials of type 2 diabetes and obesity is most evident in individuals with higher baseline BP [1,5,6] and may be attributable to reductions in tubular sodium reabsorption [32] or central sympathetic output [33] as well as peripheral vasodilatory effects [34]. In contrast to findings in rodents [35], GLP-1 and GLP-1R agonists do not appear to promote the secretion of atrial natriuretic peptide in humans [30,31].…”
Section: Discussionmentioning
confidence: 96%
“…It was suggested that the increase in cardiac output may be a compensatory response to vasodilatation elsewhere. The effectiveness of GLP-1R agonists in reducing BP in clinical trials of type 2 diabetes and obesity is most evident in individuals with higher baseline BP [1,5,6] and may be attributable to reductions in tubular sodium reabsorption [32] or central sympathetic output [33] as well as peripheral vasodilatory effects [34]. In contrast to findings in rodents [35], GLP-1 and GLP-1R agonists do not appear to promote the secretion of atrial natriuretic peptide in humans [30,31].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, natriuresis is induced by both SGLT2 inhibitors and GLP-1R agonists through different mechanisms; notably, the pathways and mechanisms linking GLP-1R signaling to renal sodium excretion are controversial and less well understood (7). Although short-term infusion (3 h) of GLP-1 7-36amide increases natriuresis in healthy volunteers (8,9) and in insulin-resistant obese males (8), whether these actions are sustained with chronic GLP-1R activation is unclear. Furthermore, the majority of studies examining how GLP-1R agonists increase sodium excretion are often 3-72 h in duration (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Intravenous infusion of GLP-1 increased glomerular filtration rate (GFR), inhibited proximal tubular reabsorption, and increased urine flow and Na ϩ excretion in rats (6,30). In healthy subjects, infusion of GLP-1 evoked a dose-dependent increase in urinary Na ϩ excretion without changing GFR (20,21). Studies in intact rat and porcine renal proximal tubules indicated that GLP-1 decreases Na ϩ /H ϩ exchanger (NHE3)-mediated bicarbonate reabsorption (6,34).…”
mentioning
confidence: 99%
“…Studies in humans demonstrate that obese men responded to GLP-1 infusion with a natriuresis, but, in contrast to healthy subjects, this natriuresis was associated with a decrease in GFR (21), indicating that factors related to body mass may affect the renal response to EX4 and/or DPP-4 inhibition. Therefore, we also compared the effect of EX4 and ALG on renal function in obese type 2 diabetic db/db mice.…”
mentioning
confidence: 99%